Analysis of the Influence of Work Experience, Work Morale, and Working Period on Employee Productivity at the Birem Bayeun Sub-district Office, East Aceh - Zuwanda, Ari; Aminah, Sitti; Riza, Tauviq; Shiddiq, Ady Akmal; Silvia, Yunita; Pane, Sri Gustina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Employee productivity is an important factor in achieving organizational goals, especially in the government sector. This study aims to analyze the influence of work experience, work morale, and working period on employee productivity at the Birem Bayeun Sub-district Office, East Aceh. This study uses a quantitative approach with a survey method. Data analysis was carried out using the multiple linear regression method to determine the influence of each independent variable on the dependent variable. The results of the study show that work experience has a positive and significant influence on employee productivity, which shows that the more work experience an employee has, the higher the level of productivity. Work morale has also been proven to have a significant effect on productivity, where employees with high work morale are able to complete tasks more efficiently and effectively. Meanwhile, the length of service shows a more varied influence, where a longer period of service does not necessarily guarantee increased productivity, but rather depends on the quality of the employee's experience and adaptation to change. This study concludes that the combination of adequate work experience, high work morale, and productive work period is a key factor in improving employee performance. Recommendations were given to the Birem Bayeun Sub-district Office to provide relevant training and create a supportive work environment so that employee productivity can continue to be improved.